Pencegahan Perilaku Seks Bebas Melalui Pendidikan Seks (Sex Education) Terhadap Anak-Anak Jalanan - Isdian Komalasari (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2024)
The aim of this article is to analyze the importance of preventing promiscuous sexual behavior among street children through sex education as well as analyzing legal protection rights for street children who have the same rights as the successors of the younger generation in the future. The author focuses on street children in the Bekasi City area. This research was carried out using qualitative methods and data collection was carried out using empirical and juridical approaches. The author merges into the environment of a group of street children without being contaminated by their interactions. The data collected includes several data, namely 1) factors that cause the emergence of street children, 2) the impact of not introducing sex education to street children and 3) legal protection that should protect street children from the negative impacts that could occur due to free sex. Data is measured through observations in their environment and analyzed descriptively qualitatively. The research results show that it is very important to teach and instill sex eduction in street children, because otherwise it will have negative impacts such as free sex, various crimes and the destruction of the future of the prospective young generation in the future. The results of the research conclude that sex education is very important and legal protection to protect and efforts to improve the behavior and lives of street children really need to be carried out and given attention in order to save the future of this country.